The Balinese diaspora in the multicultural society of Southeast Sulawesi - Suraya, Rahmat Sewa; Rosnon, Mohd Roslan; Rustiani, Komang Wahyu; Salniwati, Salniwati; Kadek Arni Suwedawati, Gusti Ayu (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
Multiculturalism can generally affect cultural degradation and serve as a basis for conflict. However, the Balinese tribe in Southeast Sulawesi is different. This research aims to discuss the existence of transmigrants in Jati Bali Village, West Ranometo Subdistrict, South Konawe Regency, and the existence of the Balinese amid multiculturalism in Southeast Sulawesi society. Semiotic, existential, and symbolic interactionism theories were used to reveal the problems. The data were analyzed using a critical approach with a qualitative descriptive method. The results showed that the Balinese were able to adapt, which was characterized by social interactions such as religious, socially oriented, food security-oriented, and security and orderoriented. To maintain the existence of the Balinese, they preserve Balinese customs and traditions, as evidenced by the Narayanan construction, the Balinese houses architecture, and the Ogoh-ogoh procession.